Midday meals do not impair mouse memory. Issue 1 (December 2018) - Power, Sarah; Michalik, Mateusz; Couture-Nowak, Sylvie; Kent, Brianne; Mistlberger, Ralph
Abstract Nocturnal mice fed in the middle of the light period exhibit food anticipatory rhythms of behavior and physiology under control of food-entrainable circadian clocks in the brain and body. This is presumed to be adaptive by aligning behavior and physiology with predictable mealtimes. This assumption is challenged by a report that daytime feeding schedules impair cognitive processes important for survival, including object memory and contextual fear conditioning assessed at two times of day. To further evaluate these effects, mice were restricted to a 6 h daily meal in the middle of the light or dark period and object memory was tested at four times of day. Object memory was not impaired by daytime feeding, and did not exhibit circadian variation in either group. To determine whether impairment might depend on methodology, experimental procedures used previously to detect impairment were followed. Daytime feeding induced food anticipatory rhythms and shifted hippocampal clock genes, but again did not impair object memory. Spontaneous alternation and contextual fear conditioning were also not impaired. Hippocampal memory function appears more robust to time of day and daytime feeding schedules than previously reported; day-fed mice can remember what they have seen, where they have been, and where it is dangerous.